A Bibliometric Mapping of Plant-Based Milk - M Irfan Febriansyah; Nafisah Eka Puteri; Mustafa Kamal (Jurnal Teknologi Pengolahan Pertanian, 2022)
Non-dairy or plant-based milk is one of the new food products derived from plants. It is essential to explore the plant milk market from the different raw materials that can be used, understand the different products we can obtain from plant milk, as well as improve the characteristics of the plant milk. To do the exploratory, bibliographic research can be performed. Therefore, we applied bibliographic analysis to identify and explore the most advanced technology in plant milk research. Data was collected by using Harzing's Publish or Perish (PoP), saved as CSV and RIS, filtered and refined, and then analyzed using descriptive statistics and VOSviewer. We screened 485 papers (2012-2022) related to plant-based milk from 998 publications since 1981. Related keywords or terms of screened papers were then visualized by VOSviewer into network, overlay, and density visualization map. Based on the visualization map, there were 7 clusters of plant-based milk research field. The novelty of the research covered the importance and development of plant-based milk derivate, correlation to life cycle assessment, and occurrence of milk allergy. The term “diet” became the highest density term in publication between 2012 to 2022. On the other hand, the terms “sensory attribute”, “traditional plant”, and “health benefit” became the lowest density term.